EMPLOYEE PERFORMANCE IS REVIEWED FROM DISCIPLINE, SATISFACTION, FLEXIBILITY, AND WORK ENVIRONMENT IN THE REGIONAL OFFICE OF THE DIRECTORATE GENERAL OF TAXES IN CENTRAL JAVA II - Sena Jati Semilir; Kartika Hendra Titisari; Bambang Mursito (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
The purpose of this research are to determine the influence of discipline, satisfaction, flexibility, and work environment on the employees performance. This research uses descriptive quantitative methods. Samples use saturated samples, the entire population is sampled. The sample in this study were all employees of the Regional Office of the Directorate General of Taxes in Central Java II, amounting to 152 person. Data collection is obtained through questionnaires. The data analysis technique uses multiple linear regression analysis. The results showed that (1) discipline have a positive and significant influence on employee performance, (2) satisfaction have a positive and significant influence on employee performance, (3) flexibility have insignificant influence on employee performance, (4) work environment have a positive and significant influence on employee performance